(untitled) (Publicaciones en Ciencias y Tecnología, 2013)
This work models Wikipedia and Free Software Development through a multiagent architecture for self-organizing and emergent systems called MASOES without mathematically representing the system. In that sense, each component, mechanism and process of MASOES is instanced at individual and collective levels by the observed phenomena at the modeled systems. Thus, this paper proposes a methodology to show how to model real systems using MASOES, in order to study their self-organizing and emergent properties and, later on, to facilitate the verification of these properties, mechanisms, components and social interactions for promoting collaborative work and sharing individual and collective knowledge in these systems.